Emotional Intelligence: Key to Performance Excellence - Samuel, Jyotika; Das, Bobita (International Journal of Psychosocial Rehabilitation, 2020)
Emotional Intelligence is the key to control one’s emotion. It is the capacity to monitor own as well as others’ emotions. According to Mayer & Salovey, Emotional Intelligence is a type of social intelligence that involves the ability to monitor one’s own as well as others’ emotions, to discriminate among them and to use this information to guide one’s thinking and action. (Mayer & Salovey, 1997) Emotional intelligence helps students to study other emotions, to regulate their own emotions to be more successful. The capability to recognize other emotions is the potentiality for an individual to become successful in life. Self-awareness, self-regulation, self-motivation, social awareness and, Social skill are the five stages in designing emotional intelligence. In academic field achievement requires emotional intelligence. Positive emotions increase life satisfaction by building resilience (Haga, Kraft, 2009) and Emotional Intelligence has facilitator effects on performance (Khokhar, 2009; Nikalaous & Tsaousis, 2006). Basing on this idea, the present study aims at investigating the co relational relationship exist in two variables i.e. emotional intelligence and academic performance of final year students of training college, Sambalpur (N=50). All the subjects are in age group of 20-22years. A five point scale of Emotional Intelligence will be administered to test the hypothesis. The hypothesis of the study is that there is a positive relationship between academic excellence and high emotional intelligence. The findings reveals that the highly emotional intelligent students have more academic achievement. Relevance of the investigations will focus on the positive steps to groom girl teacher-students with emotional intelligence for better development.